Is the quality of female auditors really better? Evidence based on the Chinese A-share market - Shixin Yang; Yunguo Liu; Qiongdan Mai (China Journal of Accounting Research, 2018)
Unlike previous studies in which a single index was used to measure audit quality, this study establishes a new comprehensive index to measure audit quality via Discretionary Accrual, as estimated by Jones' basic model (1991) and Audit Opinions. The former is used to measure the quality of financial statements, and the latter is used to measure the auditors' independence in the mainstream international literature. We examine whether and how an auditor's gender affects the quality of his or her audits under the framework of empathy theory and gender role socialization theory. Using a large sample of 9861 auditor-firm-year observations from Chinese A-share-listed companies from 2011 to 2015, we find that the audit quality of signed auditors shows significant gender differences: these significant gender differences differ from the findings of previous studies that female auditors could provide a higher-quality audit than male auditors; that is, in our study the audit quality of the male auditors exceeds that of the female auditors. After distinguishing the positive and negative directions of the Discretionary Accrual, we find no significant gender differences in audit quality between male and female auditors when the earnings had been adjusted upward by the client; that is, female and male auditors had the same audit risk perception. However, when the client adjusted earnings downward, which indicates a lower audit risk for the auditor, the audit quality of female auditors was significantly lower than that of the male auditors. After controlling for the age and position of the auditors, we also find that the gender differences in the auditors' audit quality decreased significantly or even disappeared when the auditor's age exceeded 45years and/or their position was manager or above. These results are consistent with the empathy theory and gender role socialization theory.
Keywords: 650; Auditor characteristics; Sex difference; Gender difference; Audit quality; Personal characteristics